Reviving Value-Discourse and its Impact on Interacting with Others: Fiqh ut-Tanzeel and Principles of Taqneen - Alsaied, Mohamad Abdullah (Journal of Ecohumanism, 2024)
The project of renewing religious thought is not only about changing the standards of discourse to align with contemporary necessities so that it becomes more acceptable to people. Rather, intellectual renewal is fundamentally based on renewing the individual, thereby edging society towards a consciousness of its civilizational context, so as to bring about a clearer understanding of the gap between inherited traditions and what is truly required today. In this context, we find ourselves before with an elusive question which loses clarity the more we try to navigate between theory and practice. This question pertains to the value-based discourse in dealing with the "other" and its associated jurisprudential approaches in thought, as well as the extent to which it aligns with the nature of a globalized society and the relationship between different groups, whether within a single nation or between culturally diverse communities.While the treatment of this topic seems more closely related to legal or political studies, or to cultural approaches generally, Islamic legal texts and the accompanying jurisprudential studies have encompassed the scholars' reasoning within a rich body of work spanning various times and places. However, today the question becomes pertinent with the evolution of communication methods and the opening of societies to relationships which dissolve all kinds of borders—whether between individuals, communities, or institutions. These are issues which necessitate a renewal in our legislative frameworks, building on jurisprudence that transcends traditional schools without sacrificing core principles. This must engage with contemporary realities in a scientific manner, while maintaining a revivalist spirit in methodology, discourse, and goals. It should balance between practical jurisprudence and codification principles, and draw positively from the humanities, all while adhering to realism and achieving public interest without compromising the general guidelines of Sharia. This is the ideal path for establishing a discourse of coexistence with the other, in order to realize the universality of Islam amidst the massive flow of information, economic transactions, and cultural exchange between societies.The issue at hand may seem manageable by questioning the possibility of renewing jurisprudence in dealing with the "other," balancing codification and practical implementation, both in terms of being rooted and also contemporary and relevant. But can we justify benefiting from sciences and knowledge outside the inherited tradition, which for centuries has been fenced with sanctity on one side, and fear of straying beyond its boundaries on the other? This leads us to ask once again: does the very idea of coexistence allow for a jurisprudential revival that bridges the gap between differing groups?